Population Structure of Blood Cockle (Anadara antiquata) in the Intertidal Zone of Sinaboi Coastal Waters, Rokan Hilir - Chairunissa, Suci Maurizka; Nasution, Syafruddin; Zulkifli, Zulkifli (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2026)
Blood cockle (Anadara antiquata) is one of the benthic organisms commonly found in intertidal ecosystems and has important ecological and economic roles in coastal areas. Information regarding its population condition is needed to support sustainable resource management. This study aimed to analyze the population structure of A. antiquata in the intertidal zone of Sinaboi coastal waters, Rokan Hilir. This research was conducted in October 2025 in the coastal waters of Sinaboi, Rokan Hilir. Sample analysis was carried out at the Marine Biology and Physical Oceanography Laboratory, Department of Marine Science, Faculty of Fisheries and Marine Science, Universitas Riau. The study used a survey method through direct observation, measurement of environmental parameters, and sampling. Sampling was conducted using purposive sampling across three intertidal subzones: lower, middle, and upper. The results showed that environmental parameters ranged from 30–32°C for temperature, 30‰ for salinity, 7 for pH, and 7–8 cm for water transparency. The sediment type was muddy with organic matter content ranging from 7.66–14.66%. The highest abundance of A. antiquata was found in the lower subzone (60,000 ind/ha), while the lowest was in the middle subzone (46,000 ind/ha). Statistical analysis indicated no significant difference in abundance among subzones (p > 0.05). Shell size ranged from 18.1–57.4 mm and was dominated by small and medium size categories